Introducing an AKI predictive tool for patients undergoing orthopaedic surgery. Issue 1 (29th March 2019) - Baird, David Paul; Rae, Fraser; Beecroft, Christina; Gallagher, Katherine; Sim, Stephanie; Vaessen, Robert; Wright, Emily; Bell, Samira
Abstract : Patients undergoing surgery are at increased risk of acute kidney injury (AKI). AKI is associated with adverse outcomes such as increased mortality and future risk of developing chronic kidney disease. We have developed a validated preoperative scoring tool to predict postoperative AKI in patients undergoing orthopaedic surgery using seven readily available parameters. The aim of this project was to establish the use of this scoring tool with a target compliance of 80% in patients undergoing orthopaedic surgery requiring an overnight stay at Perth Royal Infirmary, a district general hospital in NHS Tayside. We created an intervention bundle for patients at high risk of AKI, which we defined as greater than 10%. An electronic tool available on smartphones and desktop computers was developed that can be used to calculate the score. The interventions were incorporated into the electronic tool and posters outlining the intervention were placed in clinical areas. Patients undergoing elective procedures were scored in the preassessment clinic while emergency patients were scored by the admitting doctors. The score was introduced using four PDSA cycles. This confirmed that the scoring tool functioned well and was being used accurately. Compliance for patients undergoing elective surgery was reasonable at 19/24 (79%) in the third and fourth PDSA cycles but was poorer for emergency admissions with compliance of only 3/7 (43%). There was excellent compliance with the suggested medication changes and postoperative blood test monitoring as advised by our intervention bundle for those at high risk of AKI. Fluid balance monitoring was advised for all patients but the outcome was similar following our intervention at 27/41 (66%) compared with 23/37 (62%) in the baseline data collection. Compliance with fluid balance monitoring was higher in patients at high risk of AKI (9/12, 75%).